Recent Developments in Our Knowledge of Inner Magnetosphere‐Ionosphere Convection. Issue 9 (28th September 2018) - Kunduri, B. S. R.; Baker, J. B. H.; Ruohoniemi, J. M.; Sazykin, S.; Oksavik, K.; Maimaiti, M.; Chi, P. J.; Engebretson, M. J.
Abstract: Plasma convection in the coupled inner magnetosphere‐ionosphere is influenced by different factors such as neutral winds, penetration electric fields, and polarization electric fields. Several crucial insights about the dynamics in the region have been derived by interpreting observations in conjunction with numerical simulations, and recent expansion in ground‐ and space‐based measurements in the region along with improvements in theoretical modeling has fueled renewed interest in the subject. In this paper we present a comprehensive review of the literature with an emphasis on studies since 2012 relevant to the National Science Foundation Geospace Environment Modeling program. We cover four specific areas: (1) the subauroral polarization stream, (2) penetration electric fields, (3) the disturbance dynamo, and (4) quiet time subauroral convection. We summarize new observations and resulting insights relevant to each of these topics and discuss various outstanding issues and unanswered questions. Key Points: Subauroral convection is driven by complex interactions involving neutral winds, penetration electric fields, and polarization electric fields Key results on subauroral convection are summarized, with an emphasis on studies related to the SIMIC focus group of the NSF GEM program Modeling quiet geomagnetic conditions in conjunction with observations is necessary to understand the physics behind subauroral convection